Intraventricular Hemorrhage Severity as a Predictor of Outcome in Intracerebral Hemorrhage - Trifan, Gabriela; Arshi, Baback; Testai, Fernando D. (Frontiers in Neurology, 2019)
Background/Objective: Intraventricular hemorrhage (IVH) extension after spontaneous supratentorial intracerebral hemorrhage (sICH) is an independent predictor of worse outcome. However, there is a paucity of data looking at the degree of IVH severity and its impact on outcome. This study addresses the contribution of IVH severity to outcome at time of hospital discharge after sICH. Methods: Two hundred and ten patients were included in the study. Baseline demographic and radiologic characteristics were abstracted. First available CT scans were reviewed for hematoma volume and location, IVH extension and presence of hydrocephalus (HCP). IVH severity was calculated using Graeb scale. Multivariate logistic regression models were developed to investigate the association of IVH severity with poor outcomes at hospital discharge, defined as modified Rankin scale score (mRS) >3. Results: Fifty-three percent of patients had IVH extension while 18% had surgical procedures done. Poor outcome (mRS >3) was seen for 56% of patients. Median IVH extension severity on the Graeb scale was two. Presence of IVH was associated with poor outcome in univariate and multivariate analysis (p < 0.005). Compared to patients with no IVH, IVH severity influenced outcome only when Graeb scores were ≥5 (OR = 1.3, 95% CI 0.49–3.23, p = 0.63, and OR = 2.9, 95% CI, 1.1–7.6, p = 0.03 for Graeb <5 and ≥5, respectively. Conclusions: Higher IVH severity (defined as Graeb score ≥5) is associated with worse outcome at time of hospital discharge, while lower IVH severity (Graeb scores 1–4) has similar outcomes to patients without IVH. IVH severity should be used in favor of IVH presence for prognostication purposes.